Atherothrombotic out-of hospital cardiac arrest: watch out for a second train. (8th February 2018) - Petruescu, Laura; Picard, Fabien; Cariou, Alain; Varenne, Olivier
Abstract : A 63-year-old man presented with an out-of-hospital cardiac arrest. The coronary angiogram with intravascular imaging was performed and showed a mid-left anterior descending artery atherosclerotic cap rupture with thrombus burden treated with drug-eluting stent (DES) implantation. During the hospitalisation in the intensive care unit, the patient experienced recurrent ventricular fibrillations and asystole with transient ST-segment elevation in the inferior leads with normal coronary angiography. A methylergonovine provocative test was therefore performed and showed an occlusive right coronary artery (RCA) spasm. Due to recurrent RCA spasm, the patient was treated with DES implantation with favourable results at 3-month follow-up.